Tranicos- Centro logístico de transporte - Núcleo de desarrollo logístico providencia de Guanentá San Gil – Santander (2018)
The development of the urban and architectural project aims to supply the needs that San Gil and the Santander region have today. Given the transport mobility indexes, it was decided to give special treatment to this infrastructure from a unit of action focused on this subject "transport and mobility" Linked to the mobility plan where the arrival of a logistic transport center is proposed to plan, implement and control the flow and storage of raw materials, semi-finished or finished products, and to manage the related information from the place from origin to place of consumption, with the purpose of satisfying customer requirements and helping micro-enterprises to meet their export or import needs, generating added value either in advertising or in product delivery quality or until production.